Didactic Obstacles in Trigonometric Ratios: Insights into Students’ Mathematical Understanding - Silfia Hayuningrat; Didi Suryadi; Imam Rofiki (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
This study examines the relationship between the knowledge prescribed in the school curriculum, the knowledge enacted by mathematics teachers, and the knowledge constructed by students in learning trigonometric ratios through the perspective of Didactic Transposition Theory. A qualitative intrinsic case study was conducted with one mathematics teacher and 22 tenth-grade students in an Indonesian senior high school. Data were collected from curriculum documents, teaching notes, classroom observations, interviews, and two tests designed to capture students’ conceptual understanding. The data were analyzed using document analysis, content analysis, and descriptive analysis. The findings show that although students’ understanding of trigonometric ratios improved during instruction, the enacted classroom practices mainly emphasized trigonometric ratios as fixed relationships among the sides of right triangles. Consequently, students tended to interpret sine, cosine, and tangent primarily as geometric ratios rather than as functions of angles. This emphasis limited students’ ability to connect geometric reasoning with functional interpretations of trigonometric relationships. These results highlight the importance of strengthening instructional coherence in curriculum implementation so that classroom teaching better supports the development of both geometric and functional understanding of trigonometry.